The Effect of Spiritual Self-Care Training on the Feeling of Comfort in Hospitalized Women: A Comprehensive Review - Munayfah Salamah Alanazi et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Spiritual self-care plays a vital role in promoting emotional well-being and enhancing comfort, particularly for hospitalized women facing physical and psychological challenges. This review explores the impact of spiritual self-care training on the comfort levels of women in healthcare settings. Emphasis is placed on the mechanisms through which spiritual practices contribute to overall well-being, recent studies evaluating intervention effectiveness, and recommendations for integrating spiritual care into clinical practice. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/273 https://doi.org/10.5281/zenodo.14480519